Acoustically induced slip in sheared granular layers: Application to dynamic earthquake triggering. Issue 22 (19th November 2015) - Ferdowsi, Behrooz; Griffa, Michele; Guyer, Robert A.; Johnson, Paul A.; Marone, Chris; Carmeliet, Jan
Abstract: A fundamental mystery in earthquake physics is "how can an earthquake be triggered by distant seismic sources?" Here we use discrete element method simulations of a granular layer, during stick slip, that is subject to transient vibrational excitation to gain further insight into the physics of dynamic earthquake triggering. Using Coulomb friction law for grains interaction, we observe delayed triggering of slip in the granular gouge. We find that at a critical vibrational amplitude (strain) there is an abrupt transition from negligible time‐advanced slip (clock advance) to full clock advance; i.e., transient vibration and triggered slip are simultaneous. The critical strain is of order 10 −6, similar to observations in the laboratory and in Earth. The transition is related to frictional weakening of the granular layer due to a dramatic decrease in coordination number and the weakening of the contact force network. Associated with this frictional weakening is a pronounced decrease in the elastic modulus of the layer. The study has important implications for mechanisms of triggered earthquakes and induced seismic events and points out the underlying processes in response of the fault gouge to dynamic transient stresses. Key Points: Clock advance of the triggered slip is a first‐order phase transition of the vibration amplitude The critical vibrational strain for triggering clock‐advanced slip is of order 10 −6 The transition is due to weakening of the granular layer and disruption of its contact network